NILAI-NILAI PENDIDIKAN ISLAM UNTUK MENINGKATKAN KARAKTER DALAM PELAYANAN BIMBINGAN DAN KONSELING - Ria Hayati (Al-Irsyad: Jurnal Pendidikan dan Konseling, 2019)
This study aims to describe the implementation of Islamic educational values to improve the character of students. Guidance and counseling services by instilling the values of Islamic education need to be carried out continuously to help optimize students in behaving in accordance with the norm, independent, honest, responsible and carrying out all the commands of the Almighty and away from His prohibitions based on theQur'an and As-sunnah. The methodology in this research is descriptive with a quantitative approach. The sampling technique was purposive sampling with a sample of 38 students. Data collection techniques are distributed through Likert scale questionnaires. The total number of items as many as 36 items relating to the values of Islamic education in improving student character. The collected data were analyzed using a percentage statistical formula. Procedures for implementing BK services in implementing Islamic educational values include the following: (1) lecturers associateeach material with Islamic educational values that will shape the character of students by playing games, telling stories, drawing, giving examples, expressing themselves, discussing student data in accordance with the needs assessment (2) expressing students 'feelings / ideas, / thoughts, (3) exploring students' feelings / ideas / thoughts, (4) discussing the results of exploring / deepening their feelings / ideas / thoughts withconcepts Islamic education, (5) students plan behaviors that will be carried out in the future.Keyword: Islamic Education Values, Character, Guidance and Counseling.